Preliminary Reflexion on Road Basic Components for Road Infrastructure Preservation Works â€“ a Review - Soemitro, Ria Asih Aryani; Suprayitno, Hitapriya (Jurnal Manajemen Aset Infrastruktur & Fasilitas, 2022)
Road Maintenance Program has been changed as Road Preservation Program. This is due to the years of permanent distress on flexible pavement even if yearly maintenance works have been always done. This concept changing give various several important questions. One of these is how the road components should be classified. Finally, it can be noted that classification must be built based on road space and road physical components and the importance level in carrying out the road function. Brief, first the basic road physical components for flowing the traffic, second the road physical components for facilitating basic public facilities that must be placed along the road network. Â The first components basically consist of pavement, drainage, sign & marking, guard-rail, shoulder. While the second components consist of greenery, and facility, such as for electrical line, telephone line, potable water pipe, gas pipe, etc.